Advanced Computing National Collaboratory HPC Infrastructure, Kabré - Gómez-Sánchez, Isaac Eduardo (2020)
Kabré supercomputer is a High Performance Computing (HPC) cluster that provides tools that are needed to execute specific projects. In this paper, we present the infrastructure of such supercomputer settled at Advanced Computing National Collaboratory (CNCA), how its structure is defined by user needs and some recommendations in order to enhance the use and development of an HPC cluster infrastructure for scientific research purposes.